Synthesis of Substituted 2-(Aminoacyl) Amino-6- Halobenzothiazoles as Possible Antimicrobial Agents - El-Haddad, A.F.; Abdel-Ghaffar, S.A.; Abbas, Y.A.; El-Naggar, A.M. (Asian Journal of Chemistry, 2010)
The synthesis of some new 2-(N-Tos-or N-Pht-aminoacyl or Tos-Gly-Gly or aminoacyl hydrochloride or N-Tos or N-Pht dipeptidyl) amino-6-bromo-(or 6-iodo-) benzothiazole derivatives is described (II-XXVII). All the synthesized compounds were tested against a number of micro-organisms and some compounds were found to possess antimicrobial properties.